Pengaruh Kualitas Produk Dan Tingkat Harga Terhadap Keputusan Membeli Hortikultura Organik di Kebun Fakultas Teknologi Pangan Pertanian Dan Perikanan Universitas Nusa Nipa - Maria Yulita Menge; Sarlina Noni; Fiator Nong (Peneliti.net, 2023)
Product quality is one of the important factors that can influence purchasing decisions. The better the quality of a product, the more it will increase consumer interest in choosing and then making a purchase. A product can be said to be of high quality if the product is able to meet and satisfy customer needs. The research was conducted in the agricultural paraktek garden from August 15 – December 17, 2022. Research objective: to find out: The Effect of Product Quality and Price Level on the Decision to Buy Organic Horticulture in the Garden of the Faculty of Food and Agricultural Technology, Nusa Nipa University. The an alysis method used is multiple linear regression analysis that diffuses to test the relationship between the dependent variable (Y) and two independent variables (X1 and X2). Based on the results of multiple linear regression analysis calculations, there is a positive and significant influence between product quality and price levels on purchasing decisions. With the calculation of the value of F count 127,621 > Ftabel 3.220 or Significance F 0.000 < 0.05, it means that simultaneously there is a positive and significant influence between Product Quality and Price Level on Purchasing Decisions.